PERAN SUPERVISI KLINIS DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SMA - Dwi Fuji Hastuti; Ninit Pujianti; Syahril; Irsyad; Novriyanti Achyar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the role of clinical supervision in enhancing the pedagogical competence of high school teachers. The study employs a qualitative approach with a literature review method, using data collection techniques thru observation, interviews, and documentation involving school principals and high school teachers. The research findings indicate that clinical supervision has been implemented thru humanistic, dialogical, and reflective approaches; however, its execution has not been optimal and consistent due to a tendency to use traditional supervisory approaches that are instructive and evaluative in nature, as well as weak follow-up on supervision. This study concludes that clinical supervision plays an important role in enhancing the pedagogical competence of high school teachers; however, it needs to be implemented systematically, collaboratively, and sustainably to provide a comprehensive improvement in teachers' pedagogical competence.